Modernism in dispute art since the forties - Wood, Paul; Frascina, Francis; Harris, Jonathan; Harrison, Charles (Modern art - practices and debates, 1993)
This is the final volume in a series of four books about art and its interpretation from the mid-nineteenth century to the end of the twentieth. The books seek to explain the most important issues confronting any study of modern art, without attempting exhaustive coverage. They present a range of approaches characteristic of current art-historical debates. This fourth volume focuses on art since the 1930s, the main emphasis being on the period since the Second World War. The first chapter, 'Modernism and culture in the USA, 1930-1960', examines the ideological interests that governed the predominant Modernist account of the period. It establishes a different perspective by considering the connection between 'historical' and 'theoretical' debates in terms of the relationships between art, culture and society in the USA. Although the two focal points are the 1930s and the years after the Second World War, questions of cultural value and power in capitalist societies are also discussed in the context of parallels to be found in conditions during the 1990s. Chapter 2, 'The politics of representation', examines debates about the practices of art, art criticism and curatorial validation since the 1940s. These practices - considered as representations of ideas, values and beliefs - were produced in a period dominated by the Cold War consensus. A major issue is whether this consensus was ruptured during the late 1960s by a counter-culture characterized by, for example, feminism and the anti-Vietnam War movement. While questions about the function of art and culture are mostly located in the specific social and political conditions existing between the 1940s and the early 1970s, issues about the legacy of this period are also considered. The final chapter, 'Modernity and Modernism reconsidered', examines the high Modernism of the 1960s and goes on to review movements such as Minimal Art, Land Art and Conceptual Art which continued or contested that tradition. It also considers various artistic forms of the 1980s and discusses the apparent revival of interest in painting. The chapter closes with an inquiry into the implications of the postmodernism debate for the practice of art today.